The second species of the Chinese Panorpodidae (Mecoptera), Panorpodes brachypodus sp. nov. - Tan, Jiangli; Hua, Baozhen (Zootaxa, 2008)
Panorpodes brachypodus Tan et Hua sp. nov. from Beibei, Chongqing, China is described and illustrated. It is the second species of Panorpodidae from China. A key to the known species of the genus Panorpodes MacLachlan is also provided.